Risking or Derisking: How Management Fees Affect Hedge Fund Risk-Taking Choices - Yin, Chengdong; Zhang, Xiaoyan (Review of Financial Studies, 2023)
Abstract Hedge fund managers’ risk-taking choices are influenced by their compensation structure. We differ from most studies that focus on incentive fees and the high-water mark by examining how management fees affect managers’ risk-taking. Our simple model shows that managers’ risk-taking is negatively related to their future management fees. Using fund-level data, we find that future management fees are the dominant component of managers’ total compensation. When the contribution of future management fees increases, managers reduce risk-taking to increase survival probabilities. Moreover, funds with higher decreasing returns to scale are more sensitive to future management fees and reduce risk-taking even more. Authors have furnished an Internet Appendix, which is available on the Oxford University Press Web site next to the link to the final published paper online.